Non‐linearly conductive ZnO microvaristors/epoxy resin composite prepared by wet winding with polyester fibre cloth. (23rd December 2021) - Yuan, Zhikang; Hu, Jun; Huang, Zhiwen; Sun, Gang; Sun, Ya; He, Jinliang
Abstract: ZnO microvaristors/epoxy resin composite has drawn great attention from academia and industry for its adjustable non‐linear conductivity, high mechanical strength, and good ageing resistance. However, the sedimentation of ZnO microvaristors in epoxy resin during preparation is the key problem, which limits its application in engineering. In this study, a novel method of wet winding with polyester fibre cloth is proposed to prepare the ZnO microvaristors/epoxy resin composite. The anti‐settling effect of ZnO microvaristors in the composite is verified by scanning electron microscopy (SEM) and thermal gravimetric analysis (TGA). The microstructure shows that ZnO microvaristors distribute uniformly in the composite, and the content difference of ZnO microvaristors at the top and bottom part is only 0.4%. The composite shows typical non‐linear conductivity, and the threshold electric field and the non‐linear coefficient decrease with the content of ZnO microvaristors, while the conductivity in the insulating state shows an increasing trend. To verify the field grading effect of the composite with non‐linear conductivity (CNC), a finite element model of a needle‐plate electrode, simulating the condition of a conductive tip in a solid insulated system, is set up. CNC can adaptively grade the electric field, which reduces the surface electric field of the needle tip by 86.6% and the highest electric field in the system by 82.1%. This wet winding method solidifies the industrial application of CNC in high‐voltage power equipment.